Role of Justice Court and Consumer Rights Protection - Larusmee, Somphum (Journal for Developing the Social and Community, 2017)
Globalization is a rapidly changing information age and dynamic interactions based on the development of rapid, broad-based communication technologies that link politics, military, economic, social, and people-to-community and remote states to each other. Innovations in various fields have taken place, particularly in the areas of highly competitive and competitive trade. Businesses have adopted modern technologies to develop their production and marketing strategies with complexity while most consumers are lacking. Knowledge of product or service quality. And lack of bargaining power to obtain equal goods or services. As well as the knowledge of modern technology of business operators, most consumers are regularly damaged. The law is based on the concept of contract based on the theory of freedom of expressions. And the sacred principle of intentional representation or specific theory of liability. Including general law on trading that. "Buyers must be careful" could not really protect the rights of consumption. In the international arena, states need to intervene in the market economy mechanism of the free capitalist economy, only to maintain a social equilibrium under the rule of law. For Thailand, the law on consumer protection has been enforced since 1979. For enforcement of consumer dispute law, the Court of Justice has the power to directly review consumer cases. But since the Thai legal system uses a written law system or a codified system. The role of the court in consumer trials to find out the truth is backed by a system of allegations. Even in the later stages of the law, the Code of Conduct for Consumer Laws specifically provides the court with a role to play in the search for truth. But since judges are still familiar with the strict neutrality of the allegations, it makes sense to consider in some cases. Sometimes evidence in complex cases is not entirely true, as a result of discretion. The unconstitutional ruling was criticized by relevant and academic law and medical experts. While this type of court case management mechanism is not yet ready for effective litigation management innovation. And the potential of the people involved directly. This article focuses on the development of the role of the Court of Justice in protecting the rights of consumers in the modern world which will result in justice by adhering to the rule of law, the main role of the judiciary, is to protect the rights of consumers according to the intent. Of true law, the proposal has proposed to the court to play a leading role in the reform of the judiciary for consumer cases as follows: Improve and develop the management by providing a central agency responsible for consumer cases to collect the case management case for research and develops (R&D) the consumer trial of the Appeal Court or the Court of Appeals for unity. It has the criteria for clear discretion to be the same standard. Improve and develop the management of individuals by improving the capacity of judges to conduct consumer trial continuously. Specializes in case law such as economy, finance, banking, engineering, etc., as well as support research and development of knowledge in a variety of cases. Develop a handbook on consumer behavior for judges to modernize judicial decisions. Develop the capacity of law enforcement officials to continue. It also encourages the development of routine work to research (Routine to Research) to bring the research to the development of the work, resulting in the development of people and work to the learning organization (Learning Organization). Information technology development applications to increase channels for consumer litigation since the class filed the complaint. Complaints about the lawsuit through such channels without the need to travel to court in accordance with the principle of speed, economy and efficiency. Applications should include up-to-date information to educate consumers about consumer protection around.